TERAPI PSIKOSPIRITUAL INTERVENSI SPIRITUAL ISLAM TERHADAP WARGA BINAAN PEMASYARAKATAN (WBP) NARKOBA LAPAS KELAS IIA AMBARAWA - Khoiriyah, Siti; Mustajab, Abdullah Azam; Andriany, Megah (Jurnal Ilmiah Kesehatan, 2023)
Pupose of providing this therapy is to reduce anxiety in drug addicts so that they can live their lives calmly and be better in the future. The mental impact felt by drug users is that they often have feelings of fear, unease, heart palpitations and anxiety. Islamic spiritual intervention psychospiritual therapy is one of the therapies that can be given to reduce anxiety. Method the study uses a case study approach. Providing psychospiritual therapy with Islamic spiritual intervention to 5 drug inmates at Class II A Ambarawa Prison by providing therapy with five daily prayers and reading the Qur’an. Islamic spiritual intervention in congregational prayers and reading the Qur’an in collaboration with Ustadz assigned by the Ministry of Religion. Results before being given Islamic spiritual intervention therapy were 67% of WBP who said they were not active in religious activities, did not pray five times a day, did not read the Qur’an and felt anxious. After being given Islamic spiritual intervention therapy, 5 (100%) respondents were active in religious activities, 5 (100%) prayed 5 times a day, 3 (67%) read the Qur’an and 3 (67%) felt no anxiety. Conclusion carrying out psychospiritual therapy, Islamic spiritual interventions such as praying five times a day and reading the Qur’an, apart from getting peace, is also worth worshiping.